The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5812/ircmj.55686
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Sexual Dysfunction with Prenatal Stress and Quality of Life: A Path Analysis

Abstract: Background: Women are exposed to different stressors in life. Physical, emotional, and economic stressors of pregnancy might negatively affect couples' emotional and sexual intimacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…As a result, marital satisfaction is attained by couples [23]. Alidost et al, in their study, demonstrated that after sexual counselling, the mean score of sexual satisfaction in the posttest and the 6-month follow-up was significantly higher than that of the pre-test score [9]. The present study results are similar to the above findings and suggest that PLISSIT model-based sexual counselling increases sexual satisfaction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a result, marital satisfaction is attained by couples [23]. Alidost et al, in their study, demonstrated that after sexual counselling, the mean score of sexual satisfaction in the posttest and the 6-month follow-up was significantly higher than that of the pre-test score [9]. The present study results are similar to the above findings and suggest that PLISSIT model-based sexual counselling increases sexual satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…Sexual satisfaction during pregnancy and sexual information about this period are significantly associated with each other in many aspects, and most people do not receive sufficient information from health providers during pregnancy [7,8]. Paying attention to the sexual health of couples, recognising their concerns, helping to address these concerns and improving sexual function should be the mainstream of care during pregnancy [9]. In addition, individuals must learn the skills needed for satisfactory sexual relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In some developing countries, sexual intimacy is prohibited for a long time after childbirth, and in modern countries, due to insufficient postpartum care that causes awareness of couples, sexual intimacy does not exist (32). Alidost et al investigated the association between sexual function and prenatal stress and quality of life on 300 pregnant women aged 15 -45 years and showed that there was no significant association between education level and sexual function (23) that was similar to present study's findings. Also, the results of El-Esway & Hanafy, in this regard, were in line with the results of the two aforementioned studies (28).…”
Section: Discussionsupporting
confidence: 86%
“…It has also been shown that HRQoL might be compromised during pregnancy and that higher physical fitness plays a positive role in HRQoL . As the IFIS is a rather simple and quick‐to‐use tool that could be implemented in clinical practice, it is of clinical interest to investigate whether the IFIS can discriminate between both objectively measured physical fitness and HRQoL levels in pregnant women.…”
Section: Introductionmentioning
confidence: 99%